(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The study examined the demographic variables contributing to voter turnout in Calabar Municipality, Nigeria. The study’s objectives were to investigate the relationship between age, educational level, and voting in the last two general elections in the country. The study adopted a cross-sectional research design using the multistage sampling technique to select samples. A total of 378 persons participated in the study. Data were analysed using simple percentage and logistics regression. Significant findings include that age has a statistically significant relationship with voter turnout. Also, the level of educational attainment does not have a significant relationship with voter turnout. Other factors negatively influence voter turnout, including electoral violence, long queues on election days, rigging, and the government not caring for the masses. Younger adults must be encouraged to participate in the political process in increasing numbers and for the right reasons. These findings would be helpful to policymakers in stemming the increasing decline in turnout rates toward enhanced sociopolitical development.